2010
DOI: 10.2147/cia.s3785
|View full text |Cite
|
Sign up to set email alerts
|

Review of topiramate for the treatment of epilepsy in elderly patients

Abstract: Individuals over 65 years of age experience the new onset of seizures at a prevalence rate of roughly twice that of younger adults. Differences in physiology, need of concomitant medications, and liability for cognitive deficits in this population, make the choice of anticonvulsant drugs especially important. This paper reviews topiramate (TPM), a treatment for many types of seizures, with the above risks in mind. In particular, we discuss efficacy and pharmacokinetics with emphasis on the older patient, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 89 publications
1
9
0
2
Order By: Relevance
“…Nevertheless, among TCAs, amytriptiline, and nortryptiline dose adjustment is not indicated even with a glomerular filtration rate lower than 15 mL/min [7]. Conversely, topiramate dose should be lowered in older adults even with normal creatinine levels (half of the dose should be prescribed with creatinine clearance < 70 ml/min/1.73 m 2 ), whereas agerelated changes in hepatic function alone did not result in significant clinical impact or the need for dose adjustments [8]. Atenolol and metoclopramide doses must be lowered with low creatinine clearance according to the drug monographs, while ketorolac should be avoided in patients with renal impairment.…”
Section: Pharmacokinetics and Pharmacodynamics Changes In The Elderlymentioning
confidence: 99%
“…Nevertheless, among TCAs, amytriptiline, and nortryptiline dose adjustment is not indicated even with a glomerular filtration rate lower than 15 mL/min [7]. Conversely, topiramate dose should be lowered in older adults even with normal creatinine levels (half of the dose should be prescribed with creatinine clearance < 70 ml/min/1.73 m 2 ), whereas agerelated changes in hepatic function alone did not result in significant clinical impact or the need for dose adjustments [8]. Atenolol and metoclopramide doses must be lowered with low creatinine clearance according to the drug monographs, while ketorolac should be avoided in patients with renal impairment.…”
Section: Pharmacokinetics and Pharmacodynamics Changes In The Elderlymentioning
confidence: 99%
“…In a recent review, inconclusive data were reported concerning the efficacy and tolerability of zonisamide (ZNS) in the treatment of elderly patients with epilepsy, mainly concerning cognitive side effects 42 . Few data are reported about topiramate (TPM) use in elderly, but they suggest that, despite a generally good efficacy and tolerability profile, it seems to be a second choice in treatment of epilepsy in these patients due to both its cognitive and psychiatric AEs 43,44 .…”
Section: A Short Overview On the Treatment Of Epilepsy In Elderlymentioning
confidence: 99%
“…Wesentliche spezifisch altersbedingte Einschränkungen für die Verordnung von Valproinsäure und Topiramat gibt es nicht, es liegen relativ umfangreiche Erfahrungen bei älteren Patienten aus der Epilepsietherapie vor [9]. Generell ist die Verträglichkeit von Amitriptylin im Alter wegen der anticholinergen Wirkung schlechter als bei Jüngeren.…”
Section: Prophylaxeunclassified